Pilatus und das Blut der Galiläer - Demandt, Alexander (Hyperboreus, 2017)
In Lucas 13. 1 Pilatus punished Galilean zelots, because they tried to abolish the sacriﬁce of the Roman emperor in the Temple, which later was the beginning of the Jewish War in AD 66.